TEACHER PROFESSIONAL DEVELOPMENT PRACTICES IN ANCIENT INDIA: EVIDENCE FROM UPANISHADS (C.800 BCE - C.500 BCE) - Tyagi, Chanchal; Misra, Pradeep Kumar (International Journal of Research -GRANTHAALAYAH, 2022)
It is often believed that ‘teacher professional development’ is propagated, researched and implemented by western researchers in 19th century. Contrary to these beliefs, a study of ancient Indian text Upanishads (c.800 BCE - c.500 BCE) reveal that teacher professional development practices were a part and parcel of ancient Indian education system. Present research traces a number of evidences from three Upanishads namely Chhandogya Upanishad, Prasna Upanishad, and Taittiriya Upanishad to prove that a majority of modern day teacher professional development practices were prevalent in ancient India and rishis and munis (teachers in an ancient India) were apt practitioners and beneficiaries of these practices.